The Relationship between Perceived Social Support and Quality of Life of Older Adults with Hypertension in Tangerang - Karina Megasari Winahyu; Susi Wahyuniati; Rita Sekarsari (Universitas Muhammadiyah Tangerang, 2017)
The aging population is a common situation in developing countries caused by the successful health care outcome. However, the increasing prevalence of chronic diseases, such as hypertension is the impact of physical deterioration caused by the aging process. Older adults with hypertension require social support as a source of external support to help maintain health, which could affect the quality of life. A cross-sectional study was used by recruiting 71 older adults in primary health care in Tangerang. The standardized questionnaires, including the Multidimensional Scale of Perceived Social Support (MSPSS) and World Health Organization Quality of Life (WHOQOL) -BREF were provided based upon validity and reliability. Statistical analysis was conducted by employing the Pearson Product-Moment coefficient correlation. The result showed that perceived social support was significantly positively correlated with the quality of life of older adults with hypertension. In conclusion, this study suggests that maintaining social support from family, friends, and significant other needs to be considered in achieving a better quality of life for older adults with hypertension. Keywords: Older Adult, Hypertension, Social Support, Quality of Life.